Z Transform How to Handle the Inital Condition

z transform

I have a question about the Z transform Z{x[k+1]} = X(z)z^1. How do I account for the initial condition? In continuous systems, the analogous situation is L{x'(t)} = sX(s) -x(0). I have a equation from a state space equation,
x[k+1] = (I+TA)x[k] where x[0] = 1. I want to find a closed loop solution for x[k] =?. Normally, I would take the Z transform and solve for X(z) and then convert back. However, the Z transform is not taking into account the initial condition and is resulting in a wrong answer.

Best Answer

Using the Z-transform table on this website

Z-Transform Table Section 9.2

enter image description here

The forward tap, item # 7, has the initial condition, which means for a zero input response, x[k] can be calculated to account for the initial condition in the z domain.

In this case, I was trying to calculate: Z{x[k+1] = (I+TA)x[k]}.

yields-> z(X(Z) - x(0)) = (I+TA)X(Z)

Solving for X(Z) = z*x(0) / [z-(I+TA)]

Solving x[k] = Z^-1{X(Z)} = x(0) * (1+TA)^k

Related Topic